2015
DOI: 10.1177/2050312115615147
|View full text |Cite
|
Sign up to set email alerts
|

Survey of pharmacy involvement in hospital medication reconciliation programs across the United States

Abstract: Objective:The objective of this study is to conduct a review of pertinent literature, assess pharmacy involvement in medication reconciliation, and offer insight into best practices for hospitals to implement and enhance their medication reconciliation programs.Method:Pharmacists in hospitals nationwide were asked to complete an anonymous survey via the American College of Clinical Pharmacy online database. The multiple choice survey analyzed the roles that healthcare professionals play in medication reconcili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…In addition, almost 14% (13.44%) of participants received duplicate therapy as they continued to take the same medicine prescribed in hospital ( Table 7). Duplication of medication may be attributed to the miscommunication between staff and participants, with many patients in this study unaware of which medicines were being prescribed or given to them, or they were unaware when their medicines were temporarily stopped; similar to other studies (75)(76)(77)(78).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…In addition, almost 14% (13.44%) of participants received duplicate therapy as they continued to take the same medicine prescribed in hospital ( Table 7). Duplication of medication may be attributed to the miscommunication between staff and participants, with many patients in this study unaware of which medicines were being prescribed or given to them, or they were unaware when their medicines were temporarily stopped; similar to other studies (75)(76)(77)(78).…”
Section: Discussionsupporting
confidence: 62%
“…This is a concern as the lack of patient education, communication, and transcribing home medication to prescription charts may result in treatment failure, poor prognosis and increased hospital stay (72). Furthermore, inadequate knowledge, insufficient training and increased workload of staff have also been listed as major causes of medicines discrepancies (76)(77)(78). Since physicians, nurses and pharmacists do play key roles in medication management, including ordering, monitoring and educating patients during hospitalisation, and at discharge, a multidisciplinary team approach is considered fundamental to enhance medication reconciliation, especially with errors often originating in medication histories (79).…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacists are also responsible for providing the quality of medication of use and saving hospital costs by performing medication reconciliations. 5 A systematic review by Skjot-Arkil, et al (2021) concluded that interventions led by pharmacists in the hospital setting improved the quality of medication use, which led to a reduction in hospital visits and length of stay. 6 There may be variation in other healthcare professionals' perceptions of pharmacists.…”
Section: Introductionmentioning
confidence: 99%